(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The description of the modern German fixed phrase scheme «Warum + Verb + Pron1!(?)» is given in this article. The relevance of the study is explained by the absence of the research of the object space as well as its high importance for the practice of communication. The various scientific methods were used. The fixed phrase scheme «Warum + Verb + Pron1!(?)» is described in the structural, semantic, etymological, paradigmatic, syntagmatic, stylistic, phraseological and functional aspects. The phraseological status of it and its belonging to the phraseological subsystem of language are proved. The scheme has two required components, it is characterized by the indicators of reproducibility, structural-semantic stability and integrity, idiomaticity and expressiveness, has a fixed structure serving as a model to build similar sentences-statements. In general the scheme «Warum + Verb + Pron1!(?)» is frequent enough in the practice of speech communication, due to its system and functional characteristics. Its use in colloquial speech increases the efficiency of the communication process, gives it a relaxed character. Key words: syntactic phraseology; syntactic phraseological unit; fixed phrase scheme; German DOI 10.18522/1995-0640-2020-1-123-130